Learning design for translation materials based on Realistic Mathematics Education (RME) principles using the snakes and ladders game - Ramadan, Dwi Cahya; Susanti, Ely; Zulkardi, Zulkardi; Meryansumayeka, Meryansumayeka (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2025)
This study aimed to design a learning activity for the concept of translation using the Realistic Mathematics Education approach, incorporating the Snakes and Ladders game context. This context was chosen for its familiarity with students, making it an effective bridge to understanding the abstract concept of translation. This type of research was design research, specifically a validation studies, comprising the stages of preparation, design experimentation, and retrospective analysis. The research sample involved 16 students from Al Fatah Madrasah Aliyah Palembang, Grade XI, with data collected through observation, interviews, and document analysis. The results demonstrated that the context of the Snakes and Ladders game effectively facilitated students' understanding of translation through exploration activities, sketch modelling, and mapping on the Cartesian coordinate plane. Students could identify patterns and formulate the translation rule formally with minimal guidance. This study highlights that integrating game-based contexts within the RME approach can create meaningful learning experiences while enhancing students' comprehension of abstract mathematical concepts.